I would like to be a policeman (New Dawn press UK, 2004)
In "I Would Like to Be a Policeman," young readers follow a curious child exploring the exciting world of law enforcement. Through engaging illustrations and relatable scenarios, the book highlights the important roles police officers play in keeping communities safe. With fun facts and inspiring stories, it encourages kids to dream big and consider a future in serving others.